Fatty acid composition of lagocephalus sceleratus (gmelin, 1789) (osteichthyes: tetraodontidae) - Nurullahoğlu, Zahide Ulya; Ulusoy, Esra (Marmara Üniversitesi Fen Bilimleri Dergisi, 2013)
Lagocephalus sceleratus is one of the worst invasive species in the Mediterranean Sea migrated from Red Sea and has been spreading throughout the area. The aim of this study is focusing on the potential nutritional use of this species. The long-chain polyunsaturated fatty acids docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) are beneficial for health of humans. A good natural source of these fatty acids is seafood, especially fish. In this study, total lipid content and fatty acid composition of L. sceleratus were determined. Total lipid content of dorsal muscle was found as 1,82 %. Levels of EPA (6,08%) and DHA (15,68%) were found high. These results may mean that muscle of L. sceleratus has good nutritional value. After solving the toxicity problem of L. sceleratus, consuming this species as a food source may help to prevent the ecosystem againts this invasive species.
Keywords: Lagocephalus sceleratus; fish oil; omega-3 polyunsaturated fatty acids; fatty acid composition